Pengaruh motivasi dan lingkungan kerja terhadap produktivitas kerja karyawan pada PT. Jalurpusaka Saktikumala Pangkalan Kerinci Kabupaten Pelalawan - Susi Susanti; Dewita Suryati Ningsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to determine the Influence of motivation and work environment simultaneously and partially on employee productivity at PT. Jalurpusaka Saktikumala Pangkalan Kerinci Kabupaten Pelalawan. In conducting this study the authors take the population of the entire production employees and as many as 79 people in the study population were sampled using census method. Data collection techniques in this study was through a questionnaire (questionnaire) and interviews (interviews). Analyze the data in this study using a descriptive method, also using multiple linear regression analysis. From the results of this study concluded that the motivation and the work environment influence on labor productivity at PT. Jalurpusaka Pangkalan Kerinci Saktikumala Pelalawan by 75%. The results of the simultaneous test (F test) showed that motivation and work environment simultaneously influence on employee productivity.While the partial test results (t test) showed that motivation and work environment have a significant effect on the productivity of labor at. Jalurpusaka Saktikumala Pangkalan Kerinci Kabupaten PelalawanKeywords : Motivation, Work Environment and Employee Productivity